Konseling Behavioral dengan Teknik Shaping melalui Setting Lesson Study untuk Meminimalisir Self Aggression - Sukmayanti, Ni Putu Ade Indah; Dantes, Nyoman; Dharsana, I Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2018)
This research aims to know the effectiveness of behavioral counseling theory implementation with the technique of Shaping to minimize self aggression to know the differences of students and Self Aggression among the students who provided counseling behavioral techniques shaping with students who were not given counseling behavioral the technique of shaping in students. This research is a research associate with alphabets experiment research used pretest-postest control group design. This research population is grade VIII Junior Laboratory Undiksha Singaraja. The research sample is determined by random sampling technique is simply sempel withdrawal by means of random. After doing the raffle, researchers get 2 sample i.e. the class as a class VIII-1 as experimental and class VIII-2 as a control class Methods primary data collection using the questionnaire Self Aggression with the supporting method using the methods of observation, interviews, and a diary. Hypothesis test data analysis method using t-test. The results of this research show that there are behavioral counseling theory with implementation techniques Shaping through setting lesson study effectively to minimize Self Aggression students and there is a difference Self Aggression given counselling techniques with Shaping behavioral not given.Keywords : Behavioral Counseling, techniques of Shaping, Self Aggression.